Postglacial relative sea-level history of the Prince Rupert area, British Columbia, Canada. (1st December 2016) - Letham, Bryn; Martindale, Andrew; Macdonald, Rebecca; Guiry, Eric; Jones, Jacob; Ames, Kenneth M.
Abstract: This paper presents a history of relative sea level (RSL) change for the last 15, 000 years in the Prince Rupert region on the northern coast of British Columbia, Canada. One hundred twenty-three radiocarbon ages of organic material from isolation basin cores, sediment sequence exposures, and archaeological sites having a recognized relation to past sea levels constrain postglacial RSL. The large number of new measurements relating to past sea-level provides a well constrained RSL curve that differs in significant ways from previously published results. After deglaciation following the Last Glacial Maximum, the region experienced an isostatically-induced rapid RSL drop from as much 50 m asl to as low as −6.3 m asl in as little as a few centuries between 14, 500 BP and 13, 500 BP. After a lowstand below current sea level for about 2000 years during the terminal Pleistocene, RSL rose again to a highstand at least 6 m asl after the end of the Younger Dryas. RSL slowly dropped through the Holocene to close to its current position by 2000-1500 BP, with some potential fluctuations between 3500 and 1500 BP. This study highlights variation in RSL histories across relatively short distances, which must be accounted for by local RSL reconstructions such as this one. This RSL curve aided in the identification of an 8000–9000 year old archaeological site on a 10–12 m asl terrace, which is currently the earliest dated archaeological site in the area, and it provides guidance for searching for even older archaeological remains. We highlight the utility and potential of this refined RSL history for developing surveys for other archaeological sites associated with paleoshorelines. Graphical abstract: Highlights: 123 data points constrain 15, 000 year sea level history around Prince Rupert. Sea level position varies from >50 m asl to < −6.3 m asl after deglaciation. Variation in relative sea level change exists over relatively short distances. Sea level history helps identify early Holocene archaeological sites. The oldest archaeological site recorded in area (9000 cal. BP) is identified.